Nūbat Ramal al-Māya in cultural context : the pen, the voice, the text - Davila, Carl. (Brill Studies in Middle Eastern Literatures, 2016)
In this unique edition, Carl Davila takes an original approach to the texts of the modern Moroccan Andalusian music tradition. This volume offers a literary-critical analysis and English translation of the texts of this nūba , studies their linguistic and thematic features, and compares them with key manuscripts and published anthologies. Four introductory chapters and four appendices discuss the role of orality in the tradition and the manuscripts that lie behind the print anthologies. Two supplements cross-reference key poetic images in English and Arabic, and provide information on known authors of the texts. This groundbreaking contribution will interest scholars and students of pre-modern Arabic poetry, muwashshaḥāt , Andalusian music traditions, Arabic Studies, orality, and sociolinguistics.